Visitors’ assessment on recreation activities in Poring Hot Spring, Kinabalu Park, Sabah - Samuian, Christerina (2018)
There is an increasing awareness in the Malaysian society regarding the needs in recreation activities that offers variety of experiences and benefits. The purpose of this study is to determine the respondent’s pattern on recreational activities, their preferences and the management priorities in Poring Hot Spring. The sample involved 150 respondents which includes local and foreign visitors. Most of them revealed that their main purpose of visiting Poring Hot Spring is to have fun. In addition, they also want to spend time with their family and to enhance family relationships. Based on the result, it shows that the highest percentage of respondents’ preference towards recreational activities were soaking in the outdoor hot water tubs (68%), swimming in rock pools (64.7%), visiting canopy walkway (56%), and trekking to Langanan waterfall (42.7%). However, besides new experiences, new challenges and increase family togetherness, there are also issues that prevents respondents from having fun doing recreation activities at Poring Hot Spring such as overcrowding of visitors, unclean pools and lack of facilities. Therefore, based on the results of this study, it is suggested that new recreational activities can be implement besides helping the Poring Hot Spring management under the jurisdiction of Sabah Parks to prioritize on the current issues and improve the quality of recreational activities provided in the park.